Carboplatin-induced hematuria in a patient with stage I seminoma: a case report - Patricia Capdevila; Cristobal Carrasco; Jorge Aparicio (Journal of Medical Case Reports)
Abstract Background Platinum-based antineoplastic drugs are widely used in the treatment of solid tumors. Carboplatin is a safe and efficacious adjuvant treatment for stage I seminoma following a risk-adapted treatment strategy. It consists in the administration of one or two courses for patients with one or both of rete testis involvement or tumor size more than 4 cm. Carboplatin is used with the purpose of minimizing nephrotoxicity and ototoxicity caused by cisplatin while achieving excellent results. We present a case of carboplatin-induced hematuria that led to an acute kidney injury as a rare complication. Case presentation A 48 year-old Caucasian man with no medical history and no history of renal disease presented with a painless testicular mass. He underwent an orchiectomy for stage I testicular seminoma and received one course of adjuvant carboplatin (area under the curve of 7); 2 days later, he developed frank hematuria associated with back pain. The physical examination revealed mild suprapubic tenderness and Goldflam’s sign was positive bilaterally. Blood tests did not reveal anemia, his platelet count was normal, and creatinine levels were in range. Due to persisting hematuria requiring continuous bladder irrigation, he was hospitalized to monitor renal function and was initially managed conservatively with intravenous analgesics and adequate hydration. The following day, he developed an acute kidney injury (serum creatinine 1.90 mg/dL, glomerular filtration rate 41 mL/min/m2). Transurethral cystoscopy showed a blood clot on the left urinary meatus, which was irrigated and removed, revealing a clear ureteral jet. With no further measures, creatinine started declining and back pain improved. His acute kidney injury resolved in the following 72 hours. Computed tomography urogram showed a left ureteral ectasia with an enhanced urothelium within the upper and middle ureter, suggesting ureteral obstruction. The patient improved completely and was discharged successfully. On further follow-up 2 months later, a computed tomography urogram showed a complete resolution of obstructive changes. Conclusions Hematuria and acute kidney injury are rare but clinically relevant adverse events associated with the administration of carboplatin, regardless of the administered and accumulated dose. It is crucial to recognize this event and start adequate hydration promptly to prevent further kidney damage and the need for more aggressive measures, such as ureteral stenting or percutaneous nephrostomy.